Fluoroscopic imaging: New advances. (November 2022) - Keil, H.; Trapp, O.
Abstract: Today's orthopedic surgery could not be imagined without intraoperative x-ray-based imaging. This enables surgeons to assess operative interim steps as well as the result before wound closure and finishing the procedure. Although there have been mobile C-arms used for decades, there are recent advances that do not only affect the quality of the imaging itself but also the way, the information is processed and presented. These very exciting developments will change the integration of imaging into the surgical workflows, giving options of augmented reality, reduction of radiation dose, automatized acquisition and analysis of images and low-level guidance in procedures. This paper gives a review of current innovations and possible future trends in fluoroscopic 2D and 3D imaging.